HUBUNGAN NILAI HEMATOKRIT DAN JUMLAH TROMBOSIT TERHADAP DERAJAT III DAN IV PASIEN DEMAM BERDARAH DENGUE DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2022 - Marpaung, Alexander Parlindungan; Sembiring, Lidia Henni; Silangit, Thomas (Universitas Methodist Indonesia, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease condition caused by a dengue virus infection. DENV-1, DENV-2, DENV-3, and DENV-4 are serotypes of the virus and are usually transmitted through the bite of mosquitoes from the stegomyia family, such as Aedes aegypti and Aedes albopictus. DHF often results in extraordinary events (KLB) and can lead to death. The disease can be categorized into four different clinical stages: stages I, II, III, and IV. Laboratory examination in DHF usually shows a decrease in platelet count below 100,000/µl and the presence of leaky plasma, which can be seen from the hematocrit that has increased by more than 20%. Objective to determine whether there is a relationship between hematocrit value and platelet count at degrees III and IV in DHF incidence. This type of research uses an observational analytic study with a cross-sectional approach. In the analysis, there is a significant relationship between hematocrit value and clinical degrees III and IV with a value of p = 0.043, and there is a relationship between platelet counts and clinical degrees III and IV with a value of p = 0.000. There is a relationship between hematocrit value and platelet count in clinical degrees III and IV of DHF.